Vaccination of mice with Trichinella spiralis C-type lectin elicited the protective immunity and enhanced gut epithelial barrier function. - Bo Ning Wang; Xin Zhuo Zhang; Jin Yi Wu; Zhao Yu Zhang; Pei Kun Cong; Wen Wen Zheng; Shao Rong Long; Ruo Dan Liu; Jing Cui; Zhong Quan Wang (PLoS Neglected Tropical Diseases)
Background C-type lectin (CTL) plays an important act in parasite adhesion, host's cell invasion and immune escape. Our previous studies showed that recombinant Trichinella spiralis C-type lectin (rTsCTL) mediated larval invasion of enteral mucosal epithelium. The aim of this study was to investigate protective immunity produced by vaccination with rTsCTL and its effect on gut epithelial barrier function in a mouse model. Methodology/principal finding The ELISA results showed that subcutaneous vaccination of mice with rTsCTL elicited a systemic humoral response (high levels of serum IgG, IgG1/IgG2a and IgA) and significant gut mucosal sIgA responses. The levels of Th1/Th2 cytokines (IFN-γ/IL-4) secreted from spleen, mesenteric lymph nodes and Peyer's patches were distinctly increased at 6 weeks following vaccination (P < 0.05). At one week after challenge, the numbers of goblet cells and expression level of Muc2, Muc5ac and pro-inflammatory cytokines (TNF-α and IL-1β) in gut tissues of vaccinated mice were obviously decreased, while expression of anti-inflammatory cytokines (IL-4 and IL-10) was evidently increased, compared to the infected PBS group. It is interesting that expression levels of gut epithelial tight junctions (TJs; occludin, claudin-1 and E-cad) were prominently elevated and intestinal permeability was interestingly declined in vaccinated mice. The rTsCTL-vaccinated mice exhibited a 51.69 and 48.19% reduction of intestinal adult and muscle larva burdens, respectively. The female fecundity in rTsCTL vaccinated mice was reduced by 40.51%. These findings indicated that rTsCTL vaccination impeded larval invasion and improved gut epithelial integrity and barrier function, reduced worm burdens, and relieved gut and muscle inflammation. Conclusions Vaccination of mice with rTsCTL elicited an obvious protective immunity against larval challenge, impeded larval invasion of gut mucosa, enhanced gut epithelial integrity and barrier function, reduced worm burdens; it also alleviated gut and muscle inflammation. TsCTL might be a novel candidate target molecule for anti-Trichinella vaccines.